Sero-prevalence of Hepatitis B and C virus and High Risk of Hepatotoxicity among TB/HIV Positive and HIV Negative Population in Western Cameroon - Leonard Fonkeng Sama; Olive Ismael Nganou Djinou; Elvis Chongsi Wam; Roland Bamou; Innocent Mbulli Ali; Michel Noubom; Christopher Bonglavnyuy Tume (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2017)
Background: Hepatitis and HIV are the most common co-infections in tuberculosis (TB) patients and may have an effect on the liver enzymes in these co-infected TB patients. This study aimed to determine the prevalence of Hepatitis B, C and HIV in patients infected with TB in Western Cameroon and assess the effects of co-infection on their liver function. Materials and Methods: All TB infected patients referred to the Tuberculosis Research centres, from November 2014 to July 2015, and who gave their consent were screened for Hepatitis B surface antigen (HBsAg) & Hepatitis C virus (VHC) antibodies using enzyme linked immunoabsorbent assay (ELISA). HIV infection was confi rmed using a combination of two rapid tests, namely, Combaids and Tridot. All HIV positive patients were on antiretroviral therapy during the study period. The data was entered and analysed using statistical Package for social sciences 21 (SPSS- 21), and the means and proportions were calculated. Results: Of the 189 tuberculosis patients recruited in this study, HBsAg were detected in 24 (12.7%), anti-VHC antibodies in 8 (4.23%), HIV antibodies in 62 (32.8.0%), HBsAg and anti-VHC antibodies in 1 (0.53%), HBsAg and HIV antibodies in 9 (4.9%), and anti-VHC and HIV antibodies in 2 (1.1%). Estimation of liver enzymes in all co-infected and TB patients showed that a substantial proportion of our patients had normal ALP and GGT levels whereas a substantial proportion of our patients had abnormal levels of ALT and AST with patients having up to two to three-fold. All the study groups had higher baseline AST and ALT values with VHB co-infected groups having the biggest mean values. Conclusions: The prevalence of hepatitis B and C coinfection was fairly high in this largely heterosexual population supporting the use of more careful screening methods for these viruses in tuberculosis persons in these regions. High levels of transaminases were found in our study population suggesting that all TB patient should be screened for VHB, VHC and HIV infections, then monitored carefully following the initiation of therapy.